Papain‐treated panels are a simple method for the identification of alloantibodies in multiple myeloma patients treated with anti‐CD38‐based therapies. Issue 3 (25th January 2018) - Carreño‐Tarragona, G.; Cedena, T.; Montejano, L.; Alonso, R.; Miras, F.; Valeri, A.; Rivero, A.; Lahuerta, J. J.; Martinez‐Lopez, J.
SUMMARY: Objectives: To report our 2 years of experience navigating the interference of anti‐CD38 monoclonal antibodies (MAs) in 33 patients and describe papain‐treated panels as a complementary method to dithiothreitol (DTT). Background: Novel anti‐CD38 MAs are now approved or undergoing clinical trials to evaluate their activity in patients with multiple myeloma. A concern with the use of these drugs is that they interfere with blood bank tests in a group of patients who often require blood transfusions. Methods: Clinical data and whole blood samples were collected from patients receiving daratumumab or isatuximab. Routine blood bank serological tests were performed. Results: A total of 9·1% of patients presented with alloantibodies prior to treatment. All patients exhibited nonspecific reactivity in indirect antiglobulin tests, and 26% had positive direct antiglobulin tests after beginning treatment. This interference disappeared in all patients after discontinuing treatment. Papain panels avoided this reactivity and allowed us to identify alloantibodies. Phenotyped blood units were transfused, and no patient suffered any transfusion‐related complications. Conclusion: Anti‐CD38 MAs produce nonspecific interference in blood bank tests. This interference can be overcome by various methods, including DTT or papain treatment as proposed here. These methods have limitations that can be resolved using phenotyped blood units.